2010
DOI: 10.1002/rcm.4673
|View full text |Cite
|
Sign up to set email alerts
|

Identification of isobaric product ions in electrospray ionization mass spectra of fentanyl using multistage mass spectrometry and deuterium labeling

Abstract: Isobaric product ions cannot be differentiated by exact mass determinations, although in some cases deuterium labeling can provide useful structural information for identifying isobaric ions. Proposed fragmentation pathways of fentanyl were investigated by electrospray ionization ion trap mass spectrometry coupled with deuterium labeling experiments and spectra of regiospecific deuterium labeled analogs. The major product ion of fentanyl under tandem mass spectrometry (MS/MS) conditions (m/z 188) was accounted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
50
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(62 citation statements)
references
References 17 publications
12
50
0
Order By: Relevance
“…These spectra contain the major structural fragments for each MS‐level. The distribution of product ions in Figure B is in agreement with the work of Wichitnithad et al…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…These spectra contain the major structural fragments for each MS‐level. The distribution of product ions in Figure B is in agreement with the work of Wichitnithad et al…”
Section: Resultssupporting
confidence: 91%
“…As described by Wichitnithad et al, the intermediate product ion at m/ z 188 forms through a 6‐centered rearrangement resulting in the loss of N ‐phenylpropanamide. However, based on our MS n studies, we have identified the intermediate product ion at m/ z 281 as an intermediate between the [M+H] + precursor and the fragment at m/ z 188.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations